Role of Magnesium in Migraine Prophylaxis among Females of Reproductive Age: A Safer Alternative to Teratogenic Agents - Muhammad Imran Khan, Adnan Mahmood, Sajjad Ali, Saima Shaikh, Safia Bano, Muhammad Jahangir Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Migraine is a prevalent neurological disorder, particularly affecting females of reproductive age, and is often associated with significant disability and reduced quality of life. Objective: To evaluate the effectiveness of magnesium supplementation in reducing the frequency, severity, and duration of migraines, as well as its impact on quality of life and medication usage, in females of reproductive age. Methodology: This was a prospective observational study conducted at the Department of Neurology, Sialkot Medical College Sialkot from 1st February 2023 to 31st October 2023. A total of 175 females aged 18–45 years, diagnosed with episodic or chronic migraines, were enrolled. Participants self-selected their treatment regimen: 98 participants chose magnesium supplementation (Magnesium Group), while 77 participants either did not take magnesium or opted for other treatments (Non-Magnesium Group). Results: At 6 months, the magnesium group showed significant reductions in migraine (6.4±2.3 to 3.2±1.8 days/month, p<0.01), severity (7.4±1.2 to 4.1±1.5, p<0.01), and duration (4.3±1.5 to 2.5±1.2 hours, p<0.01). The non-magnesium group showed smaller reductions in these outcomes. Additionally, the magnesium group reduced rescue medication usage (3.8±2.1 to 1.5±1.2 doses/month, p<0.01) and experienced significant improvement in quality of life (MIDAS score 28.3±12.1 to 15.4±9.3, p<0.01). Adverse effects were mild and limited to gastrointestinal discomfort in 12% of participants in the Magnesium Group, with no severe adverse events. Conclusion: Magnesium supplementation significantly reduced migraine frequency, severity, and duration, and improved quality of life in females of reproductive age. The findings support magnesium as an effective, well-tolerated strategy for migraine prophylaxis. Keywords: Role, Magnesium, Migraine Prophylaxis, Females, Reproductive age